Determination of Optimum Anti Protein Specific Concentration of 208 kDa Milk Cow on QCM Sensor - Nur Chabibah; Setyawan P. Sakti; Masdiana Ch. Padaga; Johan A. E. Noor; Fenny Irawati; Farida Wahyuni (Natural B, Journal of Health and Environmental Sciences, 2014)
The purpose of the research is to detect optimum concentration of immobilization of anti protein cow’s milk with 208 kDa molecular weight’s (anti PSS 208 kDa) by utilizing QCm (Quartz Crystal Microbalance) sensor. The purpose of research is to detect optimum concentration of immobilization of specific anti protein cow’s milk with 208 kDa molecular weight’s (anti PSS 208 kDa) by utilizing QCM (Quartz Crystal Microbalance) sensor. QCM sensor had been coated by polystiren solution of 5% which is heated until 200 ◦C. During measurement, QCM sensor place on data accuisition and QCM-Box measurement. 30 µL Anti PSS 208 kDa with concentration varied between 200 mg/L up to 1400 mg/L was dropped to QCM sensors. Frequency changes were recorded as a function of concentration of anti PSS 208 kDa. The frequency changes due to presence of anti PSS 208 kDa deposited on the surface of QCM sensor were not spontaneous, but takes time to reach steady state. As the concentration of anti PSS 208 kDa increased, so is the frequency change until it reaches saturation point at 1000 mg/L. The mass percentage of anti PSS 208 kDa deposited on QCM sensor surface is decreased with increasing anti PSS 208 kDa concentration. Therefore optimum immobilization concentration of anti PSS 208 kDa is define on frequency changes at first saturation point, that is at 1000 mg/L concentration namely 267 ± 5 Hz